PENGARUH PANDEMI COVID-19 TERHADAP MENINGKATNYA KEJAHATAN KONVENSIONAL PERSPEKTIF POLITIK KRIMINAL - Iyah Faniyah; Hendri Yahya (LPPM Universitas Ekasakti Padang, 2023)
Conventional crimes, namely: conventional/national crimes are crimes against life, property and honor that cause both physical and psychological harm, whether committed in ordinary ways or in a new dimension, which occur within the country. The effect of the Covid-19 Pandemic Period on Increasing Conventional Crime in the Legal Area of ​​the West Sumatra Regional Police is the reduction in their moral values ​​and social and economic conditions due to the pandemic. So it is not wrong to say that a person's actions for a reason are interrelated, either directly or indirectly. From a criminological point of view, the increase in crime rates during the pandemic was an action driven by the weakening economy. Criminal cases in West Sumatra that experienced an increase during the Covid-19 Pandemic were cases of Curat, Curas and Curanmor and Begal. Based on sociological theory, the existence of crime during a pandemic occurred due to an imbalance in the structure of society. There are people who are still well off and not a few people who are experiencing difficulties during the Covid-19 pandemic. Conventional Crime Control Efforts During the Covid 19 Pandemic in the Legal Area of ​​the West Sumatra Regional Police are Preemptive Efforts, namely increasing the functions of Bimas (Community Guidance and Counseling), Shabara, as well as precincts related to robbery crimes; The service and service program, namely the KAMTIBMAS (Community Order Security) safari to community leaders and village officials; Community development through Polmas (activating Polmas); and Collaborate with the mass media to convey to the public to always be vigilant against the crime of robbery.